New Evidence of Model Crop Brassica napus L. in Soil Clean-Up: Comparison of Tolerance and Accumulation of Lead and Cadmium - Mihaela Rosca; Petronela Cozma; Mariana Minut; Raluca-Maria Hlihor; Camelia Bețianu; Mariana Diaconu; Maria Gavrilescu (Plants, 2021)
The potential of the model crop Brassica napus L. (rapeseed) for the phytoremediation of soils polluted with metals was investigated at laboratory scale. The first step consists in the evaluation of the seed germination and growth of the Brassica napus L. plant in a controlled environment, followed by the determination of the photosynthetic pigments content represented by chlorophyll a and b and carotenoids. The degree of metal accumulation in rapeseed has been evaluated by the bioaccumulation factor (BAC), the bioconcentration factor (BCF) and the translocation factor (TF). Phytotoxicity tests were performed in Petri dishes with filter papers moistened with metal solutions in the range of 0 to 300 mg/L Pb(II) or Cd(II). At the highest concentration of the lead and cadmium treatments (300 mg/L), B. napus L. showed the lowest germination degree (56.67% and 43.33%, respectively). According to Tukey test results, Pb(II) concentrations of up to 300 mg/L do not significantly affect the length of the hypocotyls, whereas, in the case of Cd(II), the mean of the radicle and hypocotyl lengths of the seedlings are significantly affected compared to the mean of the control. In soil pot experiments, important changes have been obtained in the pigment content, especially in the case of cadmium. For both metals and for each treatment (100 to 1500 mg/kg Pb(II) and 1 to 30 mg/kg Cd(II)), a TF < 1 indicates an ineffective metal transfer from root to shoot. Finally, rapeseed can be considered a tolerant plant and a suitable candidate for Pb(II) and Cd(II) accumulation and for the phytostabilization of contaminated soil under the experimental conditions adopted in the present study.